Ballistic spin injection from Fe(001) into ZnSe and GaAs - Wunnicke, O; P. Mavropoulos; R. Zeller; P.H. Dederichs; Grundler, D (PHYSICAL REVIEW B, 2002)
We consider the spin injection from Fe into ZnSe and GaAs in the ballistic limit. By means of the ab initio screened Korringa-Kohn-Rostoker method we calculate the ground-state properties of epitaxial Fe\ZnSe(001) and Fe\GaAs(001) heterostructures. Three injection processes are considered: injection of hot electrons and injection of ``thermal{''} electrons with and without an interface barrier. The calculation of the conductance by the Landauer formula shows that these interfaces act like a nearly ideal spin filter, with spin polarization as high as 99%. This can be traced back to the symmetry of the band structure of Fe for normal incidence.